Wage convergence and trade - Zhou, Yixiao; Bloch, Harry (2018)
We examine differences in wage rates across countries for workers working in the same industry, distinguishing workers in the low- medium- and high-skill groups. These differences are large and show persistence over time. We ask, nonetheless, whether there is evidence of unconditional or conditional convergence, much as is done in studies of convergence in per-capita income across countries. With our focus on the micro level we expect convergence to reflect, at least in part, the degree of integration of an industry into the world economy and examine particularly the role of exposure to trade in goods and services. Our results show strong evidence of convergence in a diverse sample of 40 countries, which includes most large economies whether rich or poor. The estimated unconditional convergence rate over the period from 1995 to 2008 is about 2% per year for workers in all skill groups, though rising with exposure to imports and falling with export intensity. When we control for variation in the rate of growth of domestic production as well as for direct effects of trade exposure, we find the estimate of resulting conditional rate of convergence is not much different from the unconditional estimates even though each of the control variables impact significantly on the growth of wages relative to the convergence prediction for at least some skill level.